2022
DOI: 10.3390/cancers14194926
|View full text |Cite
|
Sign up to set email alerts
|

PRELP Regulates Cell–Cell Adhesion and EMT and Inhibits Retinoblastoma Progression

Abstract: Retinoblastoma (RB) is the most common intraocular pediatric cancer. Nearly all cases of RB are associated with mutations compromising the function of the RB1 tumor suppressor gene. We previously demonstrated that PRELP is widely downregulated in various cancers and our in vivo and in vitro analysis revealed PRELP as a novel tumor suppressor and regulator of EMT. In addition, PRELP is located at chromosome 1q31.1, around a region hypothesized to be associated with the initiation of malignancy in RB. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Interestingly, gene sets related to inflammation such as “Interferon γ response”, “Interferon α response” and “Complement” were strongly affected in Prelp −/− meninges. Cell-cell adhesion related categories, “EMT” and “Apical Junction” were significantly affected ( Figure 5E ), which suggests that the functional role of PRELP as regulator of partial EMT may be conserved across tissues ( Papadaki et al, 2020 ; Hopkins et al, 2022 ). In summary, ontological analysis proposes two main biological roles of PRELP within the meninges: cell-cell adhesion and inflammation.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Interestingly, gene sets related to inflammation such as “Interferon γ response”, “Interferon α response” and “Complement” were strongly affected in Prelp −/− meninges. Cell-cell adhesion related categories, “EMT” and “Apical Junction” were significantly affected ( Figure 5E ), which suggests that the functional role of PRELP as regulator of partial EMT may be conserved across tissues ( Papadaki et al, 2020 ; Hopkins et al, 2022 ). In summary, ontological analysis proposes two main biological roles of PRELP within the meninges: cell-cell adhesion and inflammation.…”
Section: Resultsmentioning
confidence: 95%
“…One of the proposed mechanisms of vascular leakage is activation of EndMT of vascular endothelial cells ( Sweeney et al, 2019 ), which is associated with a reduction in adherens and tight junctions. Recently, we demonstrated that PRELP has the ability to activate mesenchymal-to-epithelial transition (MET), resulting in the enhancement in bladder epithelial cell-cell and retinoblastoma cells ( Papadaki et al, 2020 ; Hopkins et al, 2022 ). As the EndMT/MEndT mechanism is largely conserved with EMT/MET, loss of PRELP may cause vascular leakage through activation of EndMT ( Saito, 2013 ; Hong et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among this group (differentially quanti-ed relative to healthy tissue), 15 proteins (higher quantities: PGS2, UGDH, ASPN, LUM, COEA1, PRELP; and lower quantitites: PDIA3, AMPL, PDIA4, B2MG, CALR, PLSL, 1A68, COR1A, D6RGG3) were commonly identied in both breast cancer tissue samples, and have been reported to be associated with the progression of breast cancer. [63][64][65][66][67][68][69][70][71][72][73][74][75][76] The quantitative trends for these proteins were consistent in both breast cancer tissues, which further validated the reliability of identication and quantication by the All-in-One pipeline.…”
Section: Analysis Of Human Breast Tissue Using the All-in-one Dmf Pip...mentioning
confidence: 85%